2007
DOI: 10.1111/j.1365-2929.2006.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical dissection as a teaching method in medical school: a review of the evidence

Abstract: More sophisticated research designs may be necessary to solve the general problem of the small measurable impact of educational interventions and to come to scientifically sound conclusions about the best way to teach gross anatomy. Such research will have to include sufficient sample sizes, the use of validated assessment instruments, and a discussion of the educational significance of measured differences. More educational research in anatomy is necessary to counterbalance emotional arguments about dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
297
1
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(321 citation statements)
references
References 38 publications
(67 reference statements)
7
297
1
16
Order By: Relevance
“…This meta-analysis revealed that speculations drawn from prior thematic reviews do not accurately depict the breadth of available evidence. Contrary to the notion that dissection shows a slight advantage over prosection (Winkelmann, 2007), our findings suggest there are no immediate benefits of implementing dissection over other instructional modalities in terms of learner achievement, as Interestingly, historical evidence suggests a profound role for dissection in health professions education. This is evidenced, in part, by the reversal of the decade old "trend" to discontinue cadaveric dissection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This meta-analysis revealed that speculations drawn from prior thematic reviews do not accurately depict the breadth of available evidence. Contrary to the notion that dissection shows a slight advantage over prosection (Winkelmann, 2007), our findings suggest there are no immediate benefits of implementing dissection over other instructional modalities in terms of learner achievement, as Interestingly, historical evidence suggests a profound role for dissection in health professions education. This is evidenced, in part, by the reversal of the decade old "trend" to discontinue cadaveric dissection.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of published studies have attempted to address these questions and, in doing so, have regularly praised the role of dissection. These studies, however, are often grounded in students' and/or educators' perceptions (Alagna et al, 1982;Kramer and Soley, 2002), rely on anecdotal evidence (Moore, 1998;Aziz et al, 2002;Miller et al, 2002), are fraught with presumed researcher bias (Winkelmann, 2007), or lack the necessary power to make generalizable conclusions (Winkelmann, 2007). Inevitably, interpreting such studies in isolation, or without the proper methodological context, can result in a skewed representation of the empirical evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Hindura et al, when comparing a conventional preparatory course with a purely integrative one, discovered that integrative learning alone is less efficient [16,17]. Integrative learning can supplement, but not replace the preparatory course [18]. In this respect we are also in agreement with Evans and Watt [19] who promote the idea that a good medical education requires the proper combination of basic learning and clinical knowledge.…”
supporting
confidence: 75%
“…Multiple reports compare problem-based learning (Azer and Eizenberg, 2007), peer teaching (Krych et al, 2005;Evans and Cuffe, 2009), team-based learning (Nieder et al, 2005), computer or web-based teaching materials (Bryner et al, 2008;Petersson et al, 2009), and clinical skills (Dusseau et al, 2008) with traditional dissection methodology. Winkelmann (2007) reviewed several novel teaching methods and found that they were mostly judged to be ''not disadvantageous'' while at the same time not achieving significantly better results than traditional teaching methods on comparable examinations.…”
Section: Introductionmentioning
confidence: 99%